Defibrillators in adult congenital heart disease: Long‐term risk of appropriate shocks, inappropriate shocks, and complications. Issue 7 (11th June 2020) - Moore, Benjamin M.; Cao, Jacob; Cordina, Rachael L.; McGuire, Mark A.; Celermajer, David S.
Abstract: Aims: Sudden cardiac death (SCD) accounts for up to 25% of deaths in the adult congenital heart disease (ACHD) population. Current guidelines for defibrillator implantation are either extrapolated from acquired cardiac disease or are based upon single lesion studies, predominantly Tetralogy of Fallot (TOF). Defibrillator‐related morbidity appears to be substantially higher in ACHD patients. Methods: We retrospectively evaluated all patients in our ACHD database who received an implantable cardioverter‐defibrillator (ICD) between 2000 and 2019, and who were ≥16 years old at time of implant. Patients were followed for appropriate shocks, inappropriate shocks, and complications. Results: Of 4748 patients in our database, 59 patients (1.2%) underwent ICD implantation. ICDs were for primary prevention in 63% and secondary prevention in 37%. Over a median follow‐up of 6.6 years, 24% received an appropriate shock, 27% an inappropriate shock, and 42% suffered a device‐related complication (annualized risks of 3.2%, 3.6%, and 5.7%, respectively). There were no significant predictors of appropriate shocks or inappropriate shocks. All appropriate shocks in primary prevention patients occurred in TOF or transposition of the great arteries (TGA) with atrial switch, typically in the presence of multiple SCD risk factors. The majority of inappropriate shocks were due to supraventricular arrhythmias. Device‐related mortality was 1.7% (0.3% per annum). Conclusions: Appropriate shocks were relatively common in an ACHD ICD population followed in the long term. Device‐related morbidity was significant. Although risk factors have been established for TOF, and to a lesser extent TGA, risk stratification for ICD implantation in ACHD remains challenging.